Case Report: Perhaps we can do more when paradoxical embolism meets thrombophilia: inspiration from a special case - Xiaomin Xue; Muhua Dai; Lisha Pang; Jiayan Li; Chunlian Ji; Jianbiao Meng; Wei Zhang (Frontiers in Cardiovascular Medicine)
This study reported a rare case of Paradoxical Embolism complicated with thrombophilia. New thrombosis still existed after active treatment, and the existence of thrombus-prone gene was confirmed by gene detection. This patient recovered after improving the treatment plan. It emphasizes the importance of genetic testing to improve the diagnosis and treatment plan. This study comprehensively recorded the whole diagnosis and treatment process, including multidisciplinary collaboration, imaging diagnosis and personalized treatment strategies, which provided valuable guidance for similar clinical cases.